Synthesis of ciprofloxacin-conjugated poly(L-lactic acid) polymer for nanofiber fabrication and antibacterial evaluation - Parwe, Sharad P.; Chaudhari, Priti N.; Mohite, Kavita K.; Selukar, Balaji S.; Nande, Smita S.; Garnaik, Baijayantimala (International Journal of Nanomedicine, 2014)
Ciprofloxacin was conjugated with polylactide (PLA) via the secondary amine group of the piperazine ring using PLA and 7-(4-(2-Chloroacetyl) piperazin-1-yl)-1-cyclopropyl-6-fluoro-1, 4-dihydro-4-oxoquinoline-3-carboxylic acid. Zinc prolinate, a biocompatible catalyst was synthesized, characterized, and used in ring opening polymerization of L-lactide. Five different kinds of OH-terminated poly(L-lactide) (two-, three-, four-, six-arm, star-shaped) homopolymers were synthesized by ring opening polymerization of L-lactide in the presence of dodecanol, glycerol, pentaerythritol, dipentaerythritol as initiator and zinc prolinate as a catalyst. The structures of the polymers and conjugates were thoroughly characterized by means of gel permeation chromatography, matrix-assisted laser desorption/ionization-time of flight mass spectrometry, and nuclear magnetic resonance spectroscopy. PLA (molecular weight = 100,000) and ciprofloxacin conjugated PLA were used for fabrication of nonwoven nanofiber mat (diameter ranges; 150-400 nm) having pore size (62-102 nm) using electrospinning. The microbiological assessment shows that the release of ciprofloxacin possesses antimicrobial activity. The drug-release behavior of the mat was studied to reveal potential application as a drug delivery system. The result shows that the ciprofloxacin release rates of the PLA conjugate nonwoven nanofiber mat could be controlled by the drug loading content and the release medium. The development of a biodegradable ciprofloxacin system, based on nonwoven nanofiber mat, should be of great interest in drug delivery systems.
Keywords: antibacterial activity; ciprofloxacin conjugated polylactides; CP-PLA; drug release; electrospinning; MDR; nonwoven nanofibers; zinc prolinate